(untitled) (Jurnal Wahana Konseling, 2025)
This study aims to explore the readiness of adolescents to become mothers who become pregnant outside of marriage, by considering various aspects of readiness to become mothers. This study uses a qualitative method with a phenomenological approach. The subjects of this study were two respondents with the characteristics of adolescent girls who became pregnant outside of marriage, aged 15-20 years. The data collection technique in this study used a semi-structured interview technique. The results of the study indicate that both respondents still need guidance in preparing for their new role as mothers for their unborn children. Considering that they are still minors and still need support from experienced people. The recommendation from the results of this study is that pregnant adolescents need special assistance that includes education related to pregnancy, child care, and emotional support so that they are better prepared to assume the role of parents, for the sake of their own future and the future generations of the nation.